Graphene : important results and applications - Wypych, George (ChemTec Publishing, 2019)
Graphene: Important Results and Applications provides an overview on the latest research in graphene production and applications. The most advanced methods of production, including chemical vapor deposition, reduction of graphene oxide, and detonation reaction are explored, as is current research results on the unique nature of graphene and its types, including morphology and thickness, mechanical properties, electrical conductivity, elastic properties of 2D and 3D structures, and more. Chapters covering the dispersion of graphene into the polymer matrix and chemical modifications and their potential applications are also featured. The book concludes with sections focusing on current and future applications.
Keywords: Graphene.; elektronické knihy; electronic books